Avaliação de desempenho econômico e modelo de remuneração hospitalar por Diagnosis Related Groups (DRG) – casuísticas cirúrgica e clínica - Canto, Mauro Roberto (Universidade do Vale do Rio dos Sinos, 2022)
All Brazilians want a health system that delivers value in health and that is sustainable. To transform the care and remuneration model it is necessary to add competencies within an Ecosystem, capable of transforming to deliver value. The use of the DRG methodology would be an advance in performance evaluation as well as the possibility of proper comparison with other hospital institutions and mainly as an alternative of hospital services payment to be used by the supplementary health sector in Brazil and in the world. The Diagnosis Related Groups (DRG's) classification system has been used in different countries with diverse health systems (Busse et al. 2011), with purposes ranging from hospital production control to research on quality of care (Braga Neto et al, 1990). However, the most common use of DRG is in the method of payment for hospitals known as Prospective Payment System which refers to the method of payment in which the amount of payment for services is established prior to their provision and the hospital, (or other service provider) is thus partially at risk of loss or possibility of surplus, due to differences between the pre-fixed amount and the costs incurred (NORONHA et al, 1991). In this method, the value is already pre-established according to the diagnostic group (DRG) in which the patient is classified. The amount paid is based on the average cost of care for the diagnosis group in which the patient is classified, not on what was spent specifically on each patient. The DRG methodology was proposed to be used to evaluate the economic performance of surgical and clinical cases in large hospitals. The theoretical foundation emphasized five themes: DRG classification history and evolution, AP-DRG classification, performance evaluation and hospital management by DRG, hospital cost management and hospital remuneration models. The method used will consist of a single case study type research with exploratory and descriptive data approach, of quali-quantitative nature. The field of study will be Hospitals that use the DRG Brazil Platform (HPDRGB). The data will be collected from the information contained in the hospital discharge documents of each patient who underwent a surgical procedure or clinical admission, in the period of one year (April 2019 to March 2020), will be processed and extracted from the DRG Brasil Platform software version 14, initial analysis instrument, which will indicate the hospital and clinical DRGs with the highest incidence in the researched hospitals. The objectives will be: to propose, validate and present a framework that guides the implementation of the DRG method to evaluate the economic performance and remuneration model for the clinical and surgical casuistics of Hospitals of the DRG Brasil Platform (HPDRGB); to compare the economic performance and the remuneration model of the most frequent clinical and medical casuistics among the researched units using the DRG method and to identify the impacts from the implementation of the DRG method in the management of hospital services of HPDRGB.
Keywords: DRG; Diagnosis Related Groups; Performance hospitalar; Modelo de remuneração hospitalar; Hospital performance; Hospital remuneration model; ACCNPQ::Ciências Sociais Aplicadas::Administração